Pemberdayaan Perempuan Adat dalam Pelestarian Budaya Melalui Pengembangan Usaha Kreaktif Berbasis Kearifan Lokal Dengan Pemanfaatan Teknologi Digital Di Desa Talumelito Kecamatan Telaga Biru - Ansar, Ansar; Sumar, Warni Tune; Thalib, Darmawan (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2025)
Talumelito Village in Telaga Biru District, Gorontalo Regency, is a strategic village that has been designated as a Cultural Conservation Village. This village has great potential in the fields of culture, agriculture, and the creative economy. However, the community, particularly indigenous women, still faces challenges in processing corn crop yields into the traditional cake, kokole, to create value-added products, low digital literacy, and limited access to entrepreneurship and cultural preservation training. The lack of active business institutions and cultural studios also hinders the maximum development of local potential. This service program is designed as part of the Thematic Community Service Program of Gorontalo State University 2025 to empower indigenous women thru the development of creative businesses based on local wisdom and the utilization of digital technology. The activities aim to provide training in production and business management, cultural preservation, digital literacy, and health and environmental education. This program aligns with the MBKM policy and supports the achievement of university Key Performance Indicators (KPIs). With a participatory and collaborative approach, it is hoped that this program will be able to create a community of independent, tech-literate women who are actively involved in the sustainable preservation of local culture. Strengthening the role of women means creating a supportive environment where they can actively participate in cultural preservation. This includes providing access to education and training, as well as promoting gender equality in community participation.